OSMANLI DÖNEMİNDE DOĞU KARADENİZ BÖLGESİNDE KURULAN TEKKE VE ZAVİYELER - BOSTANCI, HARUN (Fırat Üniveristesi, 2007)
Tez bir giris ve iki bölümden olusmaktadır.Tezin birinci bölümünde Tekke ve Zaviyeler baslıgı altında Osmanlı Devleti'ndeki Tekke ve Zaviyelerin devletin iktisadi ve sosyal yapıya olan etkisi hakkında bilgi verilmistir.. Ayrıca bu bölümde Osmanlı Devleti'nde Tekke ve Zaviyelerin fonksiyonları islenmistir. Tezin ikinci bölümünde Osmanlı Döneminde Dogu Karadeniz Bölgesinde kurulmus olan Tekke ve Zaviyeler tarihi, sosyal, iktisadi ve dini açılardan incelenerek belgelerle izaha çalısılmıstır.. Teze sonuç, bibliyografya ilave edilerek tez tamamlanmıstır

This thesis is consisting of an introduction and two parts, in the first section, under the Small Dervish Lodges title, the information about the impressions of the small dervish lodges in the Ottoman Empire on the financial and social structure of the state have been given. Nevertless, in this section the functions of the small dervish lodges in the Ottoman Empire have been studied. In the second part of the thesis, the small dervish lodges which had been established in the East Blacksea Region in the Ottoman Empire have been clarified using official popers as historicial, social and religious.The thesis has been completed adding a result and a bibliography.
The small dervish lodges which had been established in the east blacksea region in the Ottoman Empire
Keywords: Tarih